Interleukin-4 during post-exercise recovery negatively correlates with the production of phagocyte-generated oxidants - Chmielecki, Adam; Bortnik, Krzysztof; Galczynski, Szymon; Kopacz, Karolina; Padula, Gianluca; Jerczynska, Hanna; Stawski, Robert; Nowak, Dariusz (Frontiers in Physiology, 2023)
Exhaustive run induced a biphasic oxidative response of circulating phagocytes in 16 amateur sportsmen. The first phase involved an increment just after exercise of enhanced whole blood chemiluminescence normalized per phagocyte count, whereas in the second phase a decrement from 1 h post-exercise and ongoing till 24 hours. We tested whether plasma Interleukin IL-4, IL-8, IL-10 and Tumor Necrosis Factor α concentrations change in response to exhaustive run and whether there are associations between their levels and delta resting. Moreover, IL-8 and IL-10 significantly increased immediately post-exercise and after 1 hour, but later normalized. Tumor necrosis factor α rose by 1.1-times only just after exercise. However, none of these cytokines showed any correlation with the investigated chemiluminescence. Exercise did not alter plasma concentrations of IL-4. However, pre-exercise IL-4 negatively correlated with measured luminescence just after exercise (ρ=-0.54, p< 0.05), and also tended to be negatively associated with decrements of the second phase at 1 h post-exercise ρ=-0.45, p=0.08. It is suggested that plasma IL-4, by a negative association with blood phagocytes oxidants production, could be involved in the maintenance of proper balance between oxidants and anti-oxidants during strenuous exercise and post-exercise recovery.